Synergistic effects of nutrients and light favor Nostocales over non-heterocystous cyanobacteria - Aguilera, Anabella (2017)
Blooms of Nostocales (Cyanobacteria) are thought to be invading subtropical and temperate water bodies. According to nutrient stoichiometry and physiological differences between cyanobacterial groups, the replacement of non-heterocystous species by Nostocales is favored when dissolved inorganic nitrogen decreases. However, some studies have shown different trends. We used laboratory bioassays to evaluate the concomitant effects of light and nutrient enrichment on phytoplankton assemblages dominated by non-heterocystous filamentous cyanobacteria. Three nutrient conditions (no addition, addition of phosphate, and addition of nitrate and phosphate) and two light intensities (40 and 80 µmol photon m−2 s−1) were assayed. Nostocales replaced or co-dominated with non-heterocystous species in all treatments by the end of the study. The shift in community composition towards Nostocales dominance led to an increase in species richness, which suggests that species with different eco-physiological traits may have differential impacts on diversity. The highest saxitoxin concentrations were measured in no addition treatments, which could link production to nutritional stress. Nostocales featured high phenotypic plasticity in terms of changes in average trichome volume and growth rates. These results help to have a better understanding of the conditions under which Nostocales predominance can occur.